Foods of Association Biocultural Perspectives on Foods and Beverages that Mediate Sociability - Etkin, Nina (University of Arizona Press, 2009)
This fascinating book examines the biology and culture of foods and beverages that are consumed in communal settings, with special attention to their health implications. Nina Etkin covers a wealth of topics, exploring human evolutionary history, the Slow Food movement, ritual and ceremonial foods, caffeinated beverages, spices, the street foods of Hawaii and northern Nigeria, and even bottled water. Her work is framed by a biocultural perspective that considers both the physiological implications of consumption and the cultural construction and circulation of foods.